2010
DOI: 10.1016/j.jcis.2009.12.065
|View full text |Cite
|
Sign up to set email alerts
|

PDMS spreading morphological patterns on substrates of different hydrophilicity in air vacuum and water

Abstract: In paper has been to investigate the morphological patterns and kinetics of PDMS spreading on silicon wafer using combination of techniques like ellipsometry, atomic force microscope (AFM), scanning electron microscope (SEM) and optical microscopy. A macroscopic silicone oil drops as well as PDMS water based emulsions were studied after deposition on a flat surface of silicon wafer in air, water and vacuum. Our own measurements using an imaging ellipsometer, which also clearly shows the presence of a precursor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…In contrast, for the inked stamp, where there was excess PDMS on the surface, conventional transfer of polymer on the contact region on Au did occur (see the Supporting Information, Figure S2). However, the low molecular weight PDMS also coated on the “open surface” (not in contact with the stamp) by surface diffusion, , driven by the low surface energy of the polymer relative to Au. ,, As a result, the relative thickness contrast of PDMS was small. Using SEED, the contrast between the contact and the contact region for μCP (i.e., inked) and IμCP (inkless) was 2 versus 74, indicating the latter is a better mode of printing on Au (Figure S3 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, for the inked stamp, where there was excess PDMS on the surface, conventional transfer of polymer on the contact region on Au did occur (see the Supporting Information, Figure S2). However, the low molecular weight PDMS also coated on the “open surface” (not in contact with the stamp) by surface diffusion, , driven by the low surface energy of the polymer relative to Au. ,, As a result, the relative thickness contrast of PDMS was small. Using SEED, the contrast between the contact and the contact region for μCP (i.e., inked) and IμCP (inkless) was 2 versus 74, indicating the latter is a better mode of printing on Au (Figure S3 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…30 In contrast, for the inked stamp, where there was excess PDMS on the surface, conventional transfer of polymer on the contact region on Au did occur (see the Supporting Information, Figure S2). However, the low molecular weight PDMS also coated on the "open surface" (not in contact with the stamp) by surface diffusion, 31,32 driven by the low surface energy of the polymer relative to Au. 10,15,33 As a result, the relative thickness contrast of PDMS was small.…”
Section: ■ Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The published observations of interfacial layering of ILs, including recent observations of thin IL films surrounding droplets deposited from methanol solutions, are suggestive of precursor film formation, which has been observed for conventional liquids such as polydimethylsiloxane. Precursor films are thin liquid films that spread ahead of the macroscopic droplet front on a solid surface and are known to play an important role in the macroscopic spreading of liquids; however, the influence of surface heterogeneity on precursor film formation and growth has been studied very little to date (even for molecular liquids). The negligible volatility of ILs offers a distinct advantage for studying the development of precursor films because the film growth must occur via surface diffusion alone.…”
Section: Introductionmentioning
confidence: 99%
“…Silicone oil is well known to be an excellent wetting agent for most materials [3]. However, it was found that a mica surface would meet this requirement, so long as the mica was first wet by water.…”
Section: Introductionmentioning
confidence: 99%